Identification of novel 7-methyl and cyclopentanyl branched glycerol dialkyl glycerol tetraethers in lake sediments. (December 2016) - Ding, Su; Schwab, Valérie F.; Ueberschaar, Nico; Roth, Vanessa-Nina; Lange, Markus; Xu, Yunping; Gleixner, Gerd; Pohnert, Georg
Highlights: New 7-methyl branched glycerol dialkyl glycerol tetraethers (brGDGTs) are described. New cyclopentane-moiety containing compounds are also described. These novel brGDGTs were extracted from lake sediments. Consideration of the new brGDGTs may improve brGDGT-derived proxies. Abstract: Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are bacterial membrane lipids that are widely used as valuable paleoenvironmental proxies. The recently discovered 6-methyl brGDGTs improved the accuracy of the proxies for temperature "methylation branched tetraethers (MBT)" and soil pH "cyclization branched tetraethers (CBT)". However, the calibration uncertainties are still substantial for brGDGT-derived proxies (e.g., 5 °C for MBT′5ME ). Here we report a series of novel 7-methyl brGDGT isomers that co-eluted with the known 5- and 6-methyl brGDGTs in commonly applied normal phase high performance liquid chromatography (HPLC). Using an optimized HPLC gradient the novel 7-methyl brGDGTs could be structurally characterized and quantified. Their mean relative abundance was in the range of 6% of the total brGDGTs in Chinese and Cameroon lake sediments. The 7-methyl brGDGT IIa7 correlates with sediment pH ( R 2  = 0.44, root-mean-square error = 0.26 pH unit), a result that motivates the re-analysis of brGDGTs in soils and sediments to further reassess brGDGT-based proxies and to determine the source of 7-methyl brGDGTs. In addition to the 7-methyl brGDGTs, we identified two novel pentamethylated brGDGTs based on the mass spectra of its ether-cleaved hydrocarbon products.